Legal Semiotics - Vladimir Valentinovich Kozhevnikov (Matondang Journal, 2023)
The article reveals the concept of semiotics and the stages of its formation, as well as the semiotics of law; some concepts of semiotic-legal researches are analyzed; a forecast is given from the point of view of the application of semiotics of law in the future.